ESTIMATIONS OF LIMESTONE RESOURCES USING THREE DIMENSION BLOCK KRIGING METHOD A CASE STUDY: LIMESTONE SEDIMENT AT SEMEN PADANG COMPANY - GUSMAN (NIM: 22107005), MULYA
Semen Padang Company is one of cement producer in Indonesia since 1910 in Indarung sub-district, located at Ã‚Â± 15 km east to Padang city, West Sumatera. Mining concession of Semen Padang Company are Karang Putih and Tajarang Hill. The quality of cement produced by Semen Padang Company depends on the quality of limestone used. Limestone produced by Karang Putih Hill should fulfill the specified standard. To maintain the limestone quality, we need to know the quantity and quality distribution of limestone in a block model. In this area of study, there were silica inset and basalt intrusion. The making of block model was performed by geostatistic approach using kriging method to do the estimation and modeling of limestone source quality at Karang Putih Hill. Modeling and counting of source were based on three dimension block model concept which was divided into block units with grid size 100ÃƒÂ—100ÃƒÂ—15 m which was appropriate with the size of mining block at location of the study. Variable used for limestone source estimation were CaO, SiO2 and H2O levels, according to conditions of raw material quality which has been specified. The result from variogram analysis showed that spatial characteristic of CaO, SiO2 and H2O levels in limestone had nugget effect percentage of 47,36%2, 30,92%2, dan 33,3%2 with range 145 - 230 m and range for vertical direction 21 - 40 m. Percentage (%) error of limestone estimation with confidence level 95% for CaO level were 54,74%Ã‚Â±0,04%, SiO2: 0,72%Ã‚Â±0,04% and H2O: 0,36%Ã‚Â±0,007% respectively. Limestone resource quantity estimation at Karang Putih Hill up to elevation 214 mdpl which fulfilled the standard quality of CaO level ≥ 48 %, SiO2 level < 10%, and H2O level < 6 % was 158,01 million ton, while tonnase in the form of 799,94 thousand ton of silica and 1,17 million ton of basalt.